USDA Forest Service employee demographic data for diversity and inclusion analysis, 1995-2017 - Sonya S. Sachdeva (12395245) (2025)
The USDA Forest Service, Northern Research Station's Diversity & Inclusion Science Team has been analyzing demographic diversity trends within the agency using data provided by Human Resources Management (HRM). These data are presented here and include select demographic information from HRM for all Forest Service employees between October 1995 and September 2017. Variables of note include each employee's appointment year, separation year, deputy area, job series, gender, and race/ethnicity. There are three datasets included in this data publication, each showing a slightly different view of the data. The first dataset provides both permanent and temporary employee-fiscal year level demographic and career data. The second dataset provides summary employee demographic and career data (one row for each employee) as well as other employee level metrics such as advancement and length of service for those employees who at some point in their career became permanent or were never volunteers. The last dataset identifies which employees began their career with the Forest Service through an internship/student trainee program. These data were collected to analyze diversity and inclusion trends among Forest Service employees over a thirty-year period. The intent of this work is to provide Forest Service leaders, managers, employees, as well as the scientific community, insight into the success (or lack thereof) of diversification efforts within the agency. We are also able to understand how racial/ethnic backgrounds and gender intersect to create different career outcomes. For more information on these data and this study, see Westphal et al. (2022), Sachdeva et al. (2023), and Dockry et al. (2022). These data were published on 08/29/2022. Metadata updates were made on 12/16/2024 to update reference to associated publications.